1992
DOI: 10.1136/gut.33.7.1006
|View full text |Cite
|
Sign up to set email alerts
|

Sulphasalazine induced renal failure.

Abstract: Two men with longstanding ulcerative colitis who were treated with sulphasalazine for several years and who developed chronic renal failure are reported. Renal biopsy specimens showed histological changes consistent with drug induced chronic intestinal nephritis. Extensive investigation made other causes of chronic renal failure unlikely. One of these patients underwent renal transplantation, the other has impaired but stable renal function.Case 1 A 53 year old man with total ulcerative colitis had been mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 6 publications
0
24
0
2
Order By: Relevance
“…Some investigations mentioned that the obstructive nephropathy induced by sulfasalazine might be associated with sulfonamide crystals in the kidney [39]. It has also been found that sulfasalazine nephrotoxicity might be attributed to the intratubular precipitation of sulfapyridine crystals [3]. Hence, sulfapyridine-induced renal injury might play a role in sulfasalazine-induced renal injury and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigations mentioned that the obstructive nephropathy induced by sulfasalazine might be associated with sulfonamide crystals in the kidney [39]. It has also been found that sulfasalazine nephrotoxicity might be attributed to the intratubular precipitation of sulfapyridine crystals [3]. Hence, sulfapyridine-induced renal injury might play a role in sulfasalazine-induced renal injury and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although sulfasalazine is generally considered as a safe medication [2], several cases of renal injury have been reported with sulfasalazine administration [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Renal toxicity due to 5-ASA may present as GN, minimal-change nephropathy with nephrotic syndrome and interstitial nephritis, which may be associated with nephrogenic diabetes insipidus [10,11,12,13,14,15,16,17]. In many cases, it remains unclear whether renal impairment emerges as an extraintestinal manifestation or as an adverse drug effect.…”
Section: Aminosalicylatesmentioning
confidence: 99%
“…The injury is usually reversible, but when diagnosis is delayed, it may be permanent [9,13,15]. Steroid or immunosuppressive therapy may improve renal dysfunction [9,13,14].…”
Section: Aminosalicylatesmentioning
confidence: 99%
“…2 On the other hand, some investigations indicate decrease in renal function in sulfasalazine-treated patients. 3,4 Sulfasalazine-induced renal injury has typically been presented as interstitial nephritis, glomerulonephritis, nephritic syndrome and acute renal failure. [5][6][7] Sulfasalazine-induced renal injury, might be potentially irreversible.…”
Section: Introductionmentioning
confidence: 99%